Адаптивна відповідь гороху посівного на дію стресу при проростанні за використання регуляторів росту рослин та біопрепаратів - Капінос, Марина Володимирівна; Капинос, Марина Владимировна; Kapinos, Maryna (My University, 2018)
UK: Основною передумовою для переходу насіння гороху посівного із стану вимушеного спокою в стан активного росту є достатня забеспеченність його водою за сприятливих умов навколишнього середовища. EN: The study of phyto-stimulating and adaptogenic influence of plant growth regulators and biopreparations on germination of seeds of pea seed and initial growth of roots and sprouts was conducted. It has been established that the intensity of peroxide oxidation of lipids in root tissues significantly decreases during pre-sowing treatment of seeds by the growth regulator of AKM and its mixture with the microbial preparation Risobofit, which is confirmed by a decrease in the content of MDA by 37.5% and 24% and an increase in dry matter by 23% and 37% compared to control. This indicates the adaptation of the root system to growth conditions. The intensity of the LPO in the sprout during the entire germination phase varies ambiguously, which requires further research.
Adaptive response to stress increased by the project for use of plants and biodiversity growth regulators
Keywords: рост рослин; біоприпарати; насіння гороху; регулятори росту